1993
DOI: 10.1007/bf01907984
|View full text |Cite
|
Sign up to set email alerts
|

A mathematically designed STS primer without any mismatches for direct sequencing of cosmid DNA clones

Abstract: SummaryWe report here a new method for the direct sequencing of large DNA inserts of cosmid clones from human chromosomes using STS primers of 14 nucleotides without any mismatches, which are designed from results of a mathematical analysis. It is clear that STS primer of 14 nucleotides is optimum for direct sequencing of cosmid recombinant DNA clones. We also provide examples of direct sequencing of cosmid clones of human chromosome 21 using these STS primers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Then, 13 positive clones were obtained. We confirmed that one of cosmid clones (noo 8) was the correct functional clone corresponded to a PCR-3 clone by nucleotide sequencing as described by Tang et al (1993) (data not shown; Amakawa et al, 1993;Brou et al, 1994;Hamaguchi et al, t989;Matsunami et al, 1989). A cosmid clone (no.…”
supporting
confidence: 77%
“…Then, 13 positive clones were obtained. We confirmed that one of cosmid clones (noo 8) was the correct functional clone corresponded to a PCR-3 clone by nucleotide sequencing as described by Tang et al (1993) (data not shown; Amakawa et al, 1993;Brou et al, 1994;Hamaguchi et al, t989;Matsunami et al, 1989). A cosmid clone (no.…”
supporting
confidence: 77%
“…The cosmid cloned DNAs were sequenced directly (Slightom and Sieu, 1992) by a modified method as described by Tang et al (1993).…”
Section: Methodsmentioning
confidence: 99%